PENGARUH UKURAN PERUSAHAAN, REPUTASI UNDERWRITER, RETURN ON ASSET (ROA), RETURN ON EQUITY (ROE) DAN FINANCIAL LEVERAGE TERHADAP UNDERPRICING SAHAM INITIAL PUBLIC OFFERING (IPO) PADA PASAR PERDANA DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Lestari, Yunifa Sri; Trihastuti, Adiati (JEA17: Jurnal Ekonomi Akuntansi, 2020)
ABSTRACTThe primary market is a means for companies to make an initial public offering or what is commonly known as an Initial Public Offering (IPO). There is a phenomenon in conducting an initial public offering, namely underpricing. Underpricing is a phenomenon where the initial offering price of shares is lower than the closing price of the shares on the first day on the secondary market. The purpose of this study was to determine the factors that influence the level of underpricing. The independent variables studied were company size, underwriter reputation, return on assets (ROA), return on equity (ROE) and financial leverage. The population in this study were all companies that did IPO on the Indonesia Stock Exchange in 2012-2016. The sampling technique used purposive sampling technique, namely the selection of samples with predetermined criteria, so that the samples found were 50 companies. The method of analysis in this study uses multiple linear regression. The results showed that only company size has a significant effect on underpricing, whereas, underwriter's reputation, return on assets (ROA), return on equity (ROE), and financial leverage have no significant effect on underpricing.